Investigating Students Science Knowledge and Healthy Lifestyle Behavior in Public Senior High Schools in Tanjungpinang City, Indonesia - Sarkity*, Dios; Fernando, Adam; Pratama, Yudi; Intasir, M. Pemberdi; Irawan, Bony; Sundari, Putri Dwi (Jurnal Pendidikan Sains Indonesia, 2025)
The end of the covid-19 pandemic has provided several important lessons, including the importance of understanding scientific knowledge related to healthy lifestyle behavior and the implementation of healthy lifestyle behavior itself. This study aimed to measure students' science knowledge and healthy lifestyle behavior and the differences between male and female students. This research was descriptive research with a quantitative approach. The research was carried out in August-September 2023 involving 432 public senior high school students in Tanjungpinang. Data was collected using tests and questionnaires. The data were analyzed descriptively. The results showed that students' science knowledge and healthy lifestyle behavior were generally in the good and very good categories. There were variations in the number of students in each category. The percentage of achievement of science knowledge and healthy lifestyle behavior between male and female students generally did not have that big of a difference. Even so, students' science knowledge still needs to be improved, especially through science learning